Optimizing Human Resource Management To Strengthen The Education And Social Program At Yatim Mandiri Pasuruan - Akhmad Khalim (International Journal of Education Management and Religion, 2026)
This study aims to analyze the implementation of human resource management in the development and empowerment program of Laznas Yatim Mandiri Pasuruan, a social institution that also focuses on improving the welfare and education of children in need, namely orphans and the poor. The purpose of this study is to later be able to understand the principles of human resource management that include several things, namely planning, training, strengthening motivation aimed at genius studio teachers, teacher ambassadors, and volunteers as drivers of the distribution program. This study uses a descriptive qualitative method, with data collection techniques through observation, interviews, and documentation of several key informants, such as genius studio teachers, teacher ambassadors, volunteers, and other program partners. The results of this study indicate that Laznas Yatim Mandiri Pasuruan has implemented an effective human resource strategy to ensure the sustainability and quality of its educational and social activities. Human resource planning is carried out based on program needs, while the recruitment process emphasizes the competence, commitment, and sincerity of prospective volunteers. Routine training and coaching activities are provided to improve the competence and professionalism of the human resources involved. In addition, performance assessments are carried out periodically, accompanied by the provision of non-material awards such as appreciation and recognition for the performance of volunteers and outstanding teachers.  The results of this research interview also indicate that good human resource management contributes significantly to the success of the Yatim Mandiri Pasuruan program in improving organizational effectiveness and beneficiary satisfaction. In conclusion, the implementation of human resource management at Yatim Mandiri Pasuruan plays a crucial role in creating professional, committed, and socially responsible human resources to support the mission of independence for orphans and the underprivileged.